Recent progress on femtosecond laser micro-/nano-fabrication of functional photonic structures in dielectric crystals: A brief review and perspective - Yuechen Jia; Feng Chen (APL Photonics, 2023)
Femtosecond (Fs) laser micro-/nano-fabrication technology allows direct definition of on-demand nanostructures with three-dimensional (3D) geometric features and tailored photonic functionalities in a facile manner. In addition, such a strategy is widely applicable to various material families, including dielectrics, semiconductors, and metals. Based on diverse dielectric crystals, fs-laser direct writing of optical waveguides with flexible geometries and functional waveguide-based photonic devices have been well-developed. Beyond waveguide architectures, the combination of 3D nanofabrication of fs lasers and the multi-functionalities of dielectric crystals has also lighted up the future development of novel photonic structures with features even beyond the optical diffraction limit. In this article, promising research topics on domain engineering for nonlinear optics, color centers and waveguides for integrated quantum photonics, and surface processing for integrated photonics enabled by fs laser micro-/nano-fabrication in dielectric crystals are briefly overviewed. We highlight recent progress on these research topics and stress the importance of optical aberration correction during laser fabrication, followed by a discussion of challenges and foreseeing the future development of fs laser defined nanostructures in dielectric crystals toward multi-functional photonics.